The changing view of insulin granule mobility: From conveyor belt to signaling hub - Gaus, Bastian; Brüning, Dennis; Groß, Sofie; Müller, Michael; Rustenbeck, Ingo (Frontiers in Endocrinology, 2022)
Before the advent of TIRF microscopy the fate of the insulin granule prior to release was deduced from biochemical investigations, electron microscopy and electrophysiological measurements. Since Calcium-triggered granule fusion is indisputably necessary to release insulin into the extracellular space, much effort was directed to the measure this event at the single granule level. This has also been the major application of the TIRF microscopy of the pancreatic beta cell when it became available about 20 years ago. To better understand the metabolic modulation of secretion, we were interested to characterize the entirety of the insulin granules which are localized in the vicinity of the plasma membrane to identify the characteristics which predispose to fusion. In this review we concentrate on how the description of granule mobility in the submembrane space has evolved as a result of progress in methodology. The granules are in a state of constant turnover with widely different periods of residence in this space. While granule fusion is associated with prolonged residence and decreased lateral mobility, these characteristics may not only result from binding to the plasma membrane but also from binding to the cortical actin web, which is present in the submembrane space. While granule age as such affects granule mobility and fusion probability, the preceding functional states of the beta cell leave their mark on these parameters, too. In summary, the submembrane granules represent a highly dynamic heterogeneous population which may form at least part of the metabolic memory of the beta cells.